Design and Synthesis of Hollow Nanostructures for Electrochemical Water Splitting. Issue 9 (18th January 2022) - Yang, Min; Zhang, Cai Hong; Li, Nian Wu; Luan, Deyan; Yu, Le; Lou, Xiong Wen (David)
Abstract: Electrocatalytic water splitting using renewable energy is widely considered as a clean and sustainable way to produce hydrogen as an ideal energy fuel for the future. Electrocatalysts are indispensable elements for large‐scale water electrolysis, which can efficiently accelerate electrochemical reactions occurring at both ends. Benefitting from high specific surface area, well‐defined void space, and tunable chemical compositions, hollow nanostructures can be applied as promising candidates of direct electrocatalysts or supports for loading internal or external electrocatalysts. Herein, some recent progress in the structural design of micro‐/nanostructured hollow materials as advanced electrocatalysts for water splitting is summarized. First, the design principles and corresponding strategies toward highly effective hollow electrocatalysts for oxygen/hydrogen evolution reactions are highlighted. Afterward, an overview of current reports about hollow electrocatalysts with diverse architectural designs and functionalities is given, including direct hollow electrocatalysts with single‐shelled, multi‐shelled, or open features and heterostructured electrocatalysts based on hollow hosts. Finally, some future research directions of hollow electrocatalysts for water splitting are discussed based on personal perspectives. Abstract : Hollow nanostructures with diverse architectural features and functionalities have attracted considerable interest as promising electrocatalysts for water splitting. Herein, some recent progress in the design of micro‐/nanostructured hollow structures for electrocatalytic water splitting and beyond is summarized. Special focus is taken on the direct hollow electrocatalysts with single‐shelled, multi‐shelled, or open features and heterostructured electrocatalysts based on hollow hosts.